Comparison of Shoulder Proprioception between Female Volleyball Players and Non-Athlete Females - Afsoun Nodehi-Moghaddam; Nasrin Khaki; A'aliyeh Sadat Kharazmi (University of Social Welfare and Rehabilitation Sciences, 2009)
Objective: The proprioception is important and determinant in dynamic stability of glenohumeral joint of overhead thrower in the presence of significant capsular laxity and excessive range of motion. The purpose of this study was to compare the joint position sense and kinesthesia between female volleyball players and non-athlete females in order to evaluation of their proprioception. Materials & Methods: By simple and convenient sampling 15 female volleyball players were selected from Tehran first grade teams. Also, 15 non athlete females were selected and matched by athletes and participated in this comparative and case-control study. Joint position sense and kinesthesia was measured by continuous passive movement (CPM) Fisiotek HP2 equipment. Data were analyzed by Independent T test. Results: Volleyball players demonstrated a significantly greater external rotation (P=0.035) and lower errors on joint repositioning test (P=0.017), but there was not significant difference in shoulder kinesthesia between two groups (P=0.392). Conclusion: Female volleyball players exhibited improved joint reposition abilities at external rotation mid range of motion in comparison with non-athletes females. The throwing shoulder requires the pitchers to repeatedly subject their shoulder to repetitive , forceful, circumduction motions , resulting in neuromuscular adaptation and improved proprioception.